Advanced quantitative research methods for urban planners - Ewing, Reid H.; Park, Keunhyun (New York Routledge, 2020)
"Advanced Quantitative Research Methods for Urban Planning provides fundamental knowledge and hands-on techniques about research, such as research topics and key journals in the planning field, advice for technical writing, and advanced methodologies. This book aims to provide the reader with a comprehensive and detailed understanding of advanced quantitative methods and to provide guidance on technical writing. Complex material is presented in the simplest and clearest way possible using real-world planning examples and making the theoretical content of each chapter as tangible as possible. Hands-on techniques for a variety of quantitative research studies are covered to provide doctoral students, university faculty, and professional researchers with useful guidance and references. An invaluable resource, Advanced Quantitative Research Methods for Urban Planning is an ideal read for researchers who want to branch out methodologically and practicing planners who need to conduct advanced analyses with planning data"--
Include index
Keywords: City planning; Quantitative research -- Methodology